The process of belonging: a critical autoethnographic exploration of national identity in transnational space - McCutcheon, Stephanie (Kansas State University, 2017)
The purpose of this study was to better understand constructs of national identity in transnational space by illuminating the processes and relations of national identity disruption and development. This study is pertinent as cultural and social identities are traditionally framed by nation-centric processes in education. However, the effects of globalization continue to transform education through learning abroad initiatives and changing migration behaviors, which necessitates perspectives de-centering the nation as an assumed boundary. The theoretical framework for this study was transnationalism. A transnational perspective has brought new focus to educational research and national identity development by questioning the multiculturalist assumption of nationality as stable national identity and exploring the concepts of national identity and nationalism in transnational spaces created by globalization. The methodological approach was critical autoethnography as informed by narrative inquiry, in which I critically examined my own disruptive experience as a teacher in the Marshall Islands by engaging in retellings of experiences with one of my former Marshallese students as an informant. The method of interactive interviewing with an informant was necessary to develop a critical lens and to connect individual reflexivity with writing ethnographically to relate to broader human experience. Qualitative coding methods were applied to our retellings as thematic analysis to categorize accounts in the narrative. Finally, writing as a method of inquiry and analysis was used to explore emotions, positionality, and perspective. Through iterations of performing narrative with the informant and applying narrative analysis I found that the theme of belonging was apparent as a personal feeling in our narrative. Recognizing this as the theme posed another question; how does this address the original guiding question: what is a sense of belonging in terms of relations and processes? To answer this I considered space-sensitive understandings of belonging as a transnational perspective. This conclusion reconceptualized and grounded national identity development in the materiality of belonging as a feeling to reflect (1) the material consequences of physical characteristics, (2) the allocation of resources, and (3) language as power. In curriculum and instruction, this understanding of belonging as process could reinforce the ideological inclusivity of multiculturalism while liberating constructs of identity from the constraints of the nation. This perspective could have implications on the development of students’ national and transnational identities, allowing for the recognition of diversity without diminishing issues of difference such as racism, sexism, classism, and xenophobia in society creating students capable of celebrating difference while recognizing inequity and promoting social critique.
Keywords: Transnationalism; Globalization of education; National identity disruption and development; Multiculturalism; Belonging; Student identity